2023
DOI: 10.1021/acsbiomaterials.2c01551
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced M2 Polarization of Oriented Macrophages on the P(VDF-TrFE) Film by Coupling with Electrical Stimulation

Abstract: Electrical stimulation (ES) has been considered a promising strategy in regulating intracellular communication, membrane depolarization, ion transport, etc. Meanwhile, cell topography, such as the alignment and elongation in anisotropic orientation, also plays a critical role in triggering mechanotransduction as well as the cellular fate. However, coupling of ES and cell orientation to regulate the polarization of macrophages is yet to be explored. In this work, we intended to explore the polarization of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Although the mechanism behind the M2 polarizing ability of piezoelectric materials is not well-defined, a few studies in the recent years have suggested the synergistic roles of electrical stimulation and morphology of piezoelectric materials for driving M2 polarization. Gu et al in 2023 reported that electric fields upregulate the IL-4Rα and TLR4 receptors which activate the ion channels such as TRPM7, triggering both M1 and M2 polarization . Nevertheless, the specific microstripe-like morphology of the piezoelectric material modulated the actin rearrangement and resulted in macrophage elongation, thereby increasing the expression of IL-4Rα receptor which ultimately altered the macrophages toward M2, as shown in Figure A.…”
Section: Types Of Electrical Stimulation Sources For Immunomodulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mechanism behind the M2 polarizing ability of piezoelectric materials is not well-defined, a few studies in the recent years have suggested the synergistic roles of electrical stimulation and morphology of piezoelectric materials for driving M2 polarization. Gu et al in 2023 reported that electric fields upregulate the IL-4Rα and TLR4 receptors which activate the ion channels such as TRPM7, triggering both M1 and M2 polarization . Nevertheless, the specific microstripe-like morphology of the piezoelectric material modulated the actin rearrangement and resulted in macrophage elongation, thereby increasing the expression of IL-4Rα receptor which ultimately altered the macrophages toward M2, as shown in Figure A.…”
Section: Types Of Electrical Stimulation Sources For Immunomodulationmentioning
confidence: 99%
“…(A) Synergistic effects of electrical stimulation and material morphology for promoting M2 polarization. Reproduced from ref . Copyright 2023 American Chemical Society.…”
Section: Types Of Electrical Stimulation Sources For Immunomodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexibility of 3D printing allows for the creation of complex geometries and customized structures, enabling the production of membranes tailored to specific wastewater treatment needs . The conventional methods for membrane fabrication include thermally induced phase separation (TIPS), vapor induced separation, and nonsolvent induced phase separation (NIPS) which require large quantities of solvent, toxic monomer materials, and high carbon footprint and generate large amounts of waste leading to adverse effects on human health and environment. , On the other hand, 3D printing being a sustainable method eliminates the need for solvent discharge, offering a more environmentally friendly approach and allowing the development of innovative membranes with diverse features by choosing from a wide range of materials. , The application of 3D printing technology in wastewater treatment can be traced back to 2016 when researchers from the University of Bath utilized a 3D printer to fabricate a membrane module for ultrafiltration . Since then, various kinds of 3D printing techniques, such as selective laser sintering (SLS), fused deposition modeling (FDM), solvent-based slurry stereolithography (3S), inkjet printing, and digital light processing (DLP), have been utilized for fabricating whole membranes as well as their module parts for water treatment. ,, In a typical 3D printing process, computer models prepare and direct ink to transform into 3D objects.…”
Section: Introductionmentioning
confidence: 99%
“… 4 The conventional methods for membrane fabrication include thermally induced phase separation (TIPS), vapor induced separation, and nonsolvent induced phase separation (NIPS) which require large quantities of solvent, toxic monomer materials, and high carbon footprint and generate large amounts of waste leading to adverse effects on human health and environment. 5 , 6 On the other hand, 3D printing being a sustainable method eliminates the need for solvent discharge, offering a more environmentally friendly approach and allowing the development of innovative membranes with diverse features by choosing from a wide range of materials. 4 , 7 The application of 3D printing technology in wastewater treatment can be traced back to 2016 when researchers from the University of Bath utilized a 3D printer to fabricate a membrane module for ultrafiltration.…”
Section: Introductionmentioning
confidence: 99%